Agricultural and Forestry Land and Labor Use under Long-Term Climate Change in Chile - Oscar Melo; William Foster (Atmosphere, 2021)
The appropriate design of land-use and rural employment policies depends upon the anticipated performance of the farm sector in the context of expected climate changes, especially with respect to land allocations to potential activities. Concerns over the possible net benefits of land-use changes are particularly acute in lower- and middle-income countries, where agriculture tends to be important in employment, income generation and foreign-exchange earnings. This paper presents an analysis of the expected impacts on land use in Chile of projected climate-change scenarios in 2040 and 2070. We developed a farmland allocation model with associated labor employment at the municipal level driven by expected relative net incomes per hectare, constructed from local average per-hectare yields, regional average output prices and per-hectare production cost estimates. The sensitivities of cropland allocations to relative net-income changes were estimated using historical land allocations at the municipal level derived from the last two Chilean Agricultural Censuses. The results show that the impacts of climate changes will be mitigated by land-use adaptation, the main export-earning crops tending to move south; in aggregate, agricultural employment will decrease in all the climate-change scenarios; forestry and agriculture would likely suffer a loss in net-income generation under severe climate-change scenarios.